NAVIGABILITY OF THE VISTULA AND OTHER RIVERS AS REVEALED IN PROJECTS OF POLISH ADMINISTRATIVE AUTHORITIES DURING THE EARLY 1860S - Marek RUTKOWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The aim of this article is to describe the proposals from administrators during the mid-19th century to improve the regulation of, and the rafting status on, the Vistula and other main watercourses in the Kingdom of Poland. The deliberation process is also shown, especially in order to reveal the genuine attitude of the Tsarist-controlled Polish authorities towards these requests.